Intraoperative and postoperative effects of TEG-guided platelet transfusion on antiplatelet drug-related intracerebral hemorrhage patients - Zhou, Hao (Exp Ther Med, 2019)
Intraoperative and postoperative effects of platelet transfusion on antiplatelet drug-related intracerebral hemorrhage (ICH) patients were investigated. A retrospective study on 82 ICH patients undergoing emergency surgical treatment caused by antiplatelet drugs was conducted. Among them, 51 patients treated with platelet transfusion served as the observation group and 31 patients without platelet transfusion as the control group. The intraoperative and postoperative bleeding volume, blood transfusion volume and the rate of secondary bleeding were compared between observation and control group under the guidance of thromboelastography (TEG). The coagulation routine examination results of the two groups before surgery were in the normal range, but TEG indicated an excessive inhibition of platelet function (platelet inhibition rate >89%). The platelet number after treatment increased significantly in the two groups of patients and it was significantly higher in observation group than that in control group (P<0.05). The intraoperative bleeding volume in observation group was significantly lower than that in control group. The total blood transfusion volume in observation group was significantly lower than that in control group (Z=2.681, P=0.036), the postoperative hematoma residual volume in observation group was significantly lower than that in control group (t=2.145, P=0.035), and the drainage volume in observation group was significantly lower than that in control group (t=2.401, P=0.019). Only 3.92% of the patients in observation group and 19.35% in control group had secondary surgery, and the difference of the recurrence rate of secondary bleeding between the two groups was statistically significant (χ(2)=3.610, P=0.048). TEG detection indicator can more comprehensively and accurately evaluate the preoperative coagulation function of patients. This study suggests that preoperative platelet transfusion can improve the intraoperative and postoperative bleeding of ICH patients after antiplatelet therapy to some extent, reducing the blood transfusion volume and the secondary bleeding rate.